An An Analysis of American Slang in "Dope" Movie - Syamsul Aryana Wahab; Nurhasanah Halim; Silvia Nanda Putri Erito (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2026)
Slang has been extensively examined as a sociolinguistic phenomenon and as a feature of informal communication. However, research focusing on how American slang is employed by a main character in contemporary films to construct identity and communicative meaning remains limited. This study analyzes the types and communicative functions of American slang used by the main character, Malcolm, in the film Dope (2015). Qualitative descriptive method was applied in this study. The framework used was Allan and Burridge’s (2006). It identified and classified 157 slangs. The findings reveal that the use of slangs is distributed across five primary types: Fresh and Creative, Flippant, Imitative, Clipping, and Acronym, respectively. The slangs serve several key communicative functions, including building solidarity, expressing emotions (such as anger and frustration), insulting, initiating casual conversation, creating intimacy, and conveying vivid impressions. The analysis demonstrates that Malcolm's predominant use of Fresh and Creative and Flippant slang reflects his identity as an urban teenager navigating complex social environments, while also enhancing the film's narrative authenticity and socio-cultural realism. This study concludes that slang is not merely a linguistic feature but a crucial pragmatic tool for character development and socio-cultural representation in cinematic discourse.